Parental influence in orthodontic treatment: a systematic review - Nobre, Ricardina; Pozza, Daniel H. (Medicine and Pharmacy Reports, 2023)
The reasons for searching orthodontic treatment in pediatric/adolescent patients are multifactorial. The aim of this systematic review was to study the parental influence in this process. This study comprises a systematic review of the literature, based on the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes. We analyzed 41 articles related to the study hypothesis, 29 of which followed the general inclusion criteria, and 21 specific studied the parental influence in orthodontic treatment. The results demonstrated that dental aesthetics and facial appearance were the main triggering factors related to the search for orthodontic treatment. Pair influence also plays an important role. The perception of malocclusion and the motivation are factors that emphasize the importance of parents in this process. Parental support was identified as a positive factor in orthodontic success reported in most of the studies. Parental influence has a positive effect on orthodontic treatment and should be understood by clinicians as a central factor in achieving the desired treatment plans.